1977
DOI: 10.1113/jphysiol.1977.sp012121
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the mechanism of renin release from isolated superfused rat glomeruli: effects of calcium, calcium ionophore and lanthanum

Abstract: SUMMARY1. The effects of external medium calcium concentration, the ionophore A23187 and lanthanum on the rate of renin release in vitro were studied with particular emphasis on results obtained from isolated superfused glomeruli of rat kidneys.2. The response to reduction in superfusate calcium concentration from 2 mm was a graded and reversible increase in the rate of renin release. An increase in release was detectable at 02 mm calcium; a threefold increase was found 36 mm after a change from 2 mm calcium t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
1

Year Published

1980
1980
1991
1991

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 24 publications
4
22
1
Order By: Relevance
“…Increased renin release due to a decrease in membrane bound calcium does not necessarily contradict previous results (Baumbach & Leyssac, 1977) which showed that addition ofthe ionophore A23187 to a calcium free medium reduced renin release. This reduction could be due to an increased delivery of calcium from intracellular stores to the outside, counteracting the decrease of membrane-bound calcium.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Increased renin release due to a decrease in membrane bound calcium does not necessarily contradict previous results (Baumbach & Leyssac, 1977) which showed that addition ofthe ionophore A23187 to a calcium free medium reduced renin release. This reduction could be due to an increased delivery of calcium from intracellular stores to the outside, counteracting the decrease of membrane-bound calcium.…”
Section: Discussioncontrasting
confidence: 48%
“…Thus, acute exposure to a calcium-free extracellular fluid causes an increase in renin release both from the isolated perfused intact kidney and from cortical slices and isolated glomeruli in vitro (Vandongen & Peart 1974;Baumbach & Leyssac 1977;Fray 1977;Harada, Lester & Rubin 1979). However a transient increase in renin release following addition of calcium to the perfusate after prolonged exposure to calcium-free medium has also been reported (Lester & Rubin 1977;Chen & Poisner 1976).…”
Section: Introductionmentioning
confidence: 96%
“…The results obtained are consistent with our previous observations (Baumbach & Leyssac, 1977) indicating that the process of renin release from isolated glomeruli is different from an exocytotic process, but is related to cell volume.…”
Section: Introductionsupporting
confidence: 83%
“…No experimental evidence for an effect on transmembrane calcium flux has been provided, but if the cytochalasins do actually interfere with calcium influx such an effect could explain the observed increase in osmotically provoked renin release by interference with cell volume regulation (cf. Baumbach & Leyssac, 1977).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation